2014
DOI: 10.7314/apjcp.2014.15.15.6387
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Peripheral Blood Absolute Monocyte Count in Patients with Locally Advanced or Metastatic Hepatocellular Carcinoma Receiving Systemic Chemotherapy

Abstract: In COX multivariate analysis, elevated AMC remained as an independent prognostic factor for worse OS (HR, 1.578; 95% CI, 1.120 to 2.223, p=0.009). Conclusions: Our results indiicate that circulating AMC is confirmed to be an independent prognostic factor for OS in patients with locally advanced or metastatic HCC receiving systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The circulating level of monocytes in the peripheral blood is reported to reflect the formation and/or presence of TAMs (45). Therefore, an increased level of monocytes reflects a high tumor burden in patients with cancer (5355). However, in the present study, AMC was not considered a prognostic factor for the OS rate using multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating level of monocytes in the peripheral blood is reported to reflect the formation and/or presence of TAMs (45). Therefore, an increased level of monocytes reflects a high tumor burden in patients with cancer (5355). However, in the present study, AMC was not considered a prognostic factor for the OS rate using multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After thoroughly screening the titles and abstracts by two investigators independently, the full‐texts of 173 potential studies were selected for further identification. Finally, 102 retrospective studies and 2 retrospective‐prospective studies from 93 eligible papers that met the inclusion criteria were included in this meta‐analysis 22–24,30–119 . The flow diagram of the selection procedure is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, epidemiologic studies have shown that an elevated CRP level in apparently healthy individuals can be a marker of high potential risk of certain types of cancer and that a high CRP level in cancer patients indicates a risk of earlier death by cancer [17]. PBMCs have also been linked to cancer prognosis [18]. Thus, while CRP tests act as the first-line screening for various infectious and inflammatory diseases as well as cancer and cardiovascular conditions, combining CRP detection with WBC or PBMC count and further cell analysis may lead to an improved diagnosis and prognosis.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%